Assessment of Influential Causes of Construction Project Delay in Malaysian Private Housing from Developer’s Viewpoint - Othuman Mydin, M.A.; Md Sani, N.; Agus Salim, N.A; Mohamed Alias, N. (EDP Sciences, 2014)
Project delay in the construction industry is a universal or large-scale observable fact affecting not only the construction industry but the overall economy of countries too. The objective of this study is to evaluate and identify the causes and consequences of project delays in the private housing development projects in Malaysia and the remedies that can minimize these delays. An online questionnaire survey has been carried out to collect the data and this included 76 respondents from multiple developers’ companies around Malaysia. From the survey, a total of 28 causes and 6 consequences of project delays had been identified from four different factors of delays; such as client factors, consultant factors, contractor factors and external factors, by which the contractor factor being the major contributor to this problem.The top ten causes of the delays are due to weather conditions, poor site conditions, poor site management, incomplete documents, lack of experience, financial problems, contract modifications, delay in approving of major variations, contractor coordination problem with other parties and construction mistakes and defective works. The consequences of the delays would contribute to time overrun, cost overrun, different in opinions, negotiations, legal actions and total abandonment.